2011
DOI: 10.1111/j.1600-051x.2011.01716.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of human periodontal ligament (PDL) stem cells (PDLSCs) from the inflamed PDL tissue: in vitro and in vivo evaluations

Abstract: ihPDLSCs could be successfully isolated from inflamed PDL tissue, and they retained the regenerative potential for cementum and related PDL tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
250
1
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(292 citation statements)
references
References 34 publications
26
250
1
6
Order By: Relevance
“…Due to the experimental perforation of the floor of the pulp chamber in mice, growth of chronic inflammatory granulation tissue was found to be the main tissue change without causing purulent inflammation. Recently, several studies mentioned that the cellular components of the granulation tissue were derived from the periodontal ligament stem cells (PDLSCs) [9][10][11] . We utilized bone marrow transplanted GFP mouse to analyze cell differentiation and migration in periodontal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the experimental perforation of the floor of the pulp chamber in mice, growth of chronic inflammatory granulation tissue was found to be the main tissue change without causing purulent inflammation. Recently, several studies mentioned that the cellular components of the granulation tissue were derived from the periodontal ligament stem cells (PDLSCs) [9][10][11] . We utilized bone marrow transplanted GFP mouse to analyze cell differentiation and migration in periodontal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 It has also been suggested that stem cells from an inflamed PDL still retain selfrenewal and differentiation capacities. 6 PDL cells were found to differentiate into cementoblast-like cells, osteoblast-like cells, adipocytes, and collagenforming cells in vitro, and transformed into cementum/PDL-like structures when they were transplanted with a calcium HA scaffold into immunocompromised rodents. 7 Collagen fibers from transplanted PDLSCs were able to link with the cementoblast-like structures which resemble the physiological attachment of Shapey's fibers.…”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 99%
“…[2] These cells appear localized around and adjacent to blood vessels in the PDL space, and McCulloch identifi ed them as progenitor cells. [3] These cells exhibits the characteristic smaller size than the adjacent cells, high nuclear/cytoplasmic ratio and slow cell division.…”
Section: Historymentioning
confidence: 99%
“…Extraoral sites may be bone marrow mesenchymal stem cells and adipose-derived stem cells. [2] More than any other tissue, the complexity of the periodontium along with the understanding that only certain components are capable of achieving regeneration, makes the identifi cation of stem cells important, not only in the understanding of normal wound healing events but also in designing novel clinical techniques. Seo et al [5] isolated the multipotent human PDL stem cells by single-colony selection and magnetic-activated cell sorting, and characterized according to their expression of the mesenchymal stem cell markers STRO-1 and CD 146/MUC18.…”
Section: Historymentioning
confidence: 99%